Cover Feature: Quantifying the Long‐Range Coupling of Electronic Properties in Proteins with ab initio Molecular Dynamics (Chemistry ‐ Methods 8/2021). Issue 8 (5th August 2021) - Yang, Zhongyue; Hajlasz, Natalia; Steeves, Adam H.; Kulik, Heather J.
Abstract : The Cover Feature shows a mutual information analysis of charge distributions in proteins. The presented study reveals that electronic couplings are long range in nature even between neutral amino acids. More information can be found in the Full Paper by Zhongyue Yang et al .